Visible light-triggered disruption of micelles of an amphiphilic block copolymer with BODIPY at the junction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (Chemical Communications, 2015)
A visible light-cleavable polymer is synthesised to overcome the limitations of UV-sensitive polymers. Photocleavable BODIPY functionalized with an ATRP initiator and alkyne was used to obtain an amphiphilic block copolymer by conducting the click reaction and polymerization simultaneously. Micellar assembly of the polymer was disintegrated under visible light irradiation with controlled release of cargo.